Giant snail: friend or foe? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
'The giant African snail (Achantina fulica) was introduced into my country, it is believed, during the Second World War by Japanese soldiers', writes Steven Yauiapi from Papua New Guinea where he works with Agriculture and Livestock, Vanimo Green...